(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
The urgent task for our republic is the reproduction of the health of the nation. However, the health of teenage girls today is of particular concern, since the detection of congenital and early acquired pathology has increased - the reproductive potential of the nation suffers.